Assessing the effects of gamma irradiation and storage time in energetic value and in major individual nutrients of chestnuts. - Fernandes, Ângela (2011)
Chestnut (Castanea sativa Miller) is an important food resource all over the world. In the present study, it is intended to evaluate if the application of gamma irradiation doses < 3 kGy maintain chestnuts chemical and nutritional profiles unaffected. Furthermore, possible interactions among irradiation dose and storage time were accessed using linear discriminate analysis (LDA). The nutritional composition was evaluated through determination of proteins, fat, ash, carbohydrates and energetic value. The chemical composition was focused in the main nutrients found in chestnuts: sugars- sucrose, fatty acids- palmitic, oleic, linoleic and linolenic acids, tocopherols- Y-tocopherol. The obtained results seem to indicate that the irradiation treatment did not affect the nutritional and chemical quality of chestnut fruits. Otherwise, storage time exerted more evident influence in those parameters. The application of gamma irradiation emerges as a promising technology for chestnuts chemical quality, but food safety issues has to be evaluated in order to recommend its application as a useful conservation alternative.